LAA system dynamic sub-frame configuration strategy in unlicensed bands - Wei JIANG; Shixiao LIU; Heng HU; Chenlu ZHANG (Dianxin kexue)
The use of dynamic TDD technology in heterogeneous network can effectively increase the system throughput and improve the performance of the system.Due to the limitation of signaling control and other issues,there is usually a dynamic switching between the traditional seven fixed sub-frame ratios in the licensed bands.But as a complement to the LTE system worked in the licensed bands,the unlicensed bands can achieve a more flexible and complete dynamic sub-frame configuration without considering signaling control and other issues.Two new dynamic sub-frame configuration algorithms in unlicensed bands were proposed and compared with traditional static sub-frame configuration,then the impact of dynamic sub-frame allocation algorithms on system performance was verified by LAA system level simulation platform.The results show that the proposed dynamic sub-frame configuration strategies can effectively improve the resource utilization and the overall system throughput.